Loess: Rock, sediment or soil – What is missing for its definition?. (18th April 2016) - Sprafke, Tobias; Obreht, Igor
Abstract: Loess is commonly defined as an accumulation of windblown silt. However, the complex mechanisms that are responsible for most of the structural characteristics of loess require a more precise explanation. The common definition of loess ignores a set of processes that start during and after the subaerial deposition of silt. The term loessification has been used by a number of authors to refer to the quasi-pedogenic/quasi-diagenetic processes that result in the typical aggregation of loess; however these mechanisms are rarely described in detail. Depending on the researcher's background, loess is classified as sediment, soil or rock. This review gives an overview on loess definitions through time and evaluates the main concepts related to loess formation. Several gaps of knowledge are identified that require a number of specific studies related to different aspects of loess formation in various environments. We propose to 1) differentiate primary loessification which initializes the formation of loess structure from secondary loessification which takes place subsequently and 2) define loess-like sediments as deposits that experienced loessification but were not transported aeolian. Mainly aeolian processes and loessification are of equal importance to define loess.